Enhancing Regulatory Frameworks for Islamic Banking Institutions: Comparative Study Between Indonesia and Bahrain - Fauzan Akbar; Adi Mansah (Universitas Muhammadiyah Jakarta, 2024)
This research analyzes and compares the regulatory frameworks governing Islamic Banking institutions in Bahrain, and Indonesia. The study explores how each country has developed its regulatory environment to support the growth and stability of Islamic finance, highlighting the successes, challenges, and areas for improvement. Using a qualitative comparative approach, the research draws on data from document analysis and previous studies to provide a comprehensive understanding of the regulatory landscapes in these countries. The findings reveal that Bahrain has established robust and internationally recognized regulatory frameworks, largely due to their proactive regulatory bodies and collaboration with global standard-setting organizations such as the Islamic Financial Services Board (IFSB) and the Accounting and Auditing Organization for Islamic Institutions (AAOIFI). In contrast, Indonesia, despite its significant potential, faces challenges in regulatory implementation and public literacy on Islamic finance. The study concludes that effective regulatory frameworks are crucial for the credibility and stability of Islamic finance, strengthening regulatory oversight, and adopting international standards to ensure consistent and transparent practices. This research contributes valuable insight for policymakers, regulators, and practitioners aiming to improve the regulatory environment of Islamic financial institutions globally.